Epigenetic Regulation of Transition Among Different Pluripotent States: Concise Review. (14th August 2019) - Geng, Ting; Zhang, Donghui; Jiang, Wei
Abstract : The extraordinary progress of pluripotent stem cell research provides a revolutionary avenue to understand mammalian early embryonic development. Besides well-established conventional mouse and human embryonic stem cells, the discoveries of naive state human stem cell, two-cell-like cell, and the newly defined "extended pluripotent" stem cell and "expanded potential" stem cell with bidirectional chimeric ability have greatly broadened the horizons of more pluripotent states recaptured and maintained in dish, infinitely approaching the totipotent blastomere state. Although all these pluripotent cell types can self-renew and have the ability to differentiate into all the three germ layers, accumulating evidence suggests that these pluripotent states display distinct epigenetic characters. More strikingly, epigenetic reprogramming, including DNA methylation, histone modification, and chromatin remodeling, is required to reset the cell fate commitment, suggesting that epigenetic mechanisms may play an active and important role in the maintenance and transition among these pluripotent states. Here, we have reviewed studies on various pluripotent states, with a highlight on the epigenetic regulation during the interconversion. Stem Cells 2019;37:1372–1380 : Abstract : Different pluripotent states exist and have been established in vitro, including two-cell-like cells, expanded potential stem cells and extended pluripotent stem cells, naive embryonic stem cells, and primed epiblast stem cells. Compared with postimplantation state, preimplantation state exhibits a more open chromatin structure, marked by DNA hypomethylation and enriched active histone modifications.